2022
DOI: 10.47992/ijmts.2581.6012.0246
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review on Consumer Perception and Buying Behaviour on Baby Care Products

Abstract: Purpose: Different behaviours have had a significant impact on how people shop and consume. The goal of this study is to understand consumer purchasing habits and to pinpoint the variables that affect parents' decisions to buy baby care goods. There is a shortage of knowledge regarding how consumers perceive and what factors influence customers' purchasing decisions for baby care items. Design/Methodology: Studies, case studies, journal articles, reviews and variety of research papers serve as secondary source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Pakkala and Shivashankar Bhat did a literature review about consumer perception and buying behaviors in the baby care market. In the paper, they revealed that parents stress on extensive significance of quality, hygienic standards, and safety and their purchasing decision is emotional rather than practical [4].…”
Section: Marketing In Baby Care Industrymentioning
confidence: 99%
“…Pakkala and Shivashankar Bhat did a literature review about consumer perception and buying behaviors in the baby care market. In the paper, they revealed that parents stress on extensive significance of quality, hygienic standards, and safety and their purchasing decision is emotional rather than practical [4].…”
Section: Marketing In Baby Care Industrymentioning
confidence: 99%